Umbilical cord blood thyroid hormones are inversely related to telomere length and mitochondrial DNA copy number - Homa Ohadi; Parvin Khalili; Farzaneh Abasnezhad Kasrineh; Ozra Sadat Esmaeili; Faeze Esmaeili Ranjbar; Azita Manshoori; Mohammad Reza Hajizadeh; Zahra Jalali (Scientific Reports, 2024)
Abstract Hypothyroidism has been linked to reduced mortality rate and increased lifespan and health span. Telomere shortening, enhanced oxidative stress, and reduced cellular mitochondrial content are important hallmarks of aging shown to be related to age-associated diseases. It was proposed that the status of these markers in early life can be predictive of lifespan and the predisposition to certain age-associated disease in adulthood. Animal studies indicated that prenatal injection of thyroid hormones affects postnatal telomere length. Here, we sought to determine whether thyroid hormones TSH and fT4 are related to the telomere length, mitochondrial DNA copy number (mtDNAcn), and oxidative stress resistance marker GPX in the cord blood of newborns. In this study, we analyzed 70 mothers (18–42 years) and neonate dyads born in 2022 at the Nik Nafs maternity Hospital in Rafsanjan. The relative telomere length (RTL) and mtDNAcn were measured in the genomic DNA of cord blood leukocytes using real-time PCR. GPX enzyme activity was measured in the serum using colorimetric assays. In this study the correlation between these markers and the cord blood TSH and fT4 hormones were assessed using regression models. We found a reverse relationship between TSH levels and RTL in the cord blood of neonates. Additionally, our results displayed increased TSH levels associated with enhanced GPX activity. Regarding the mitochondrial DNA copy number, we found an indirect relationship between fT4 level and mtDNAcn only in male newborns. Future analyses of various oxidative stress markers, mitochondrial biogenesis status, telomerase activity, and the level of DNA damage are warranted to demonstrate the underlying mechanism of our observations.